OrangeCode : Website to learn coding via gaming - Nasrul Arif, Zakria (2019)
Learning to code is definitely difficult without anyone explaining or visualizing it. Especially for a person who have never know any basic of coding. Studies show that there are certain person who can hardly learn something without the seeing the visual concept of it. Thus, this project will explain about the development of OrangeCode and their application. OrangeCode is a web-based online platform for the use of to understand the fundamental of coding starting from learning about variables, conditional statements, looping and more. OrangeCode can be used by any people who wanted to learn coding from the very beginning including kids. This project involves the knowledge of programming concept without referring to any specific programming language. This project was developed under the Rapid Application Development (RAD) software process model. It applied the approach of gamification and visualization to embed the concepts of coding among new learners. This approach is suitable with current world trends of video game reformation. With latest technology such as high performance computer and mobile devices, video games have become a part of lifestyle for a person especially the youths. Youths spend their day with video games whenever they have a free time. Therefore, the strategy is to convert knowledge concepts into video games so that the youths can learn while playing them. As a result from this project, students become even more interested to learn and understand programming concepts.